CRIMINAL LIABILITY OF PUBLIC OFFICIALS IN FOREIGN CRIMINAL LAW: A COMPARATIVE LEGAL ANALYSIS (World Conference on Engineering and Technological Sciences, 2026)
This thesis is devoted to a comparative legal analysis of the criminal liability of public officials in the criminal legislation of foreign states. Within the framework of the study, the criminal laws of several Western European countries, the United States, Japan, and selected Asian states are examined with regard to the legal status of public officials as subjects of crime and the grounds for their criminal liability. Particular attention is paid to corruption-related offenses and to international legal standards, primarily the provisions of the United Nations Convention against Corruption, as well as their correlation with national criminal legislation. The paper also analyzes the legal content and significance of the concepts of “public official” and “responsible official,” highlighting differences in their interpretation and application across various legal systems. The conclusions drawn in the thesis contribute to a more accurate qualification of official crimes and may serve to improve law enforcement practice and criminal legislation.
Keywords: public official, responsible official, corruption, abuse of official authority, subject of crime, special subject, comparative criminal law, criminal legislation.